Gangguan Monyet Ekor Panjang (Macaca fascicularis) Sekitar Pemukiman di Desa Tumuk Manggis dan Desa Tanjung Mekar, Kecamatan Sambas, Kalimantan Barat - Riyandi, Ozy Oriza, Tri Rima Setyawati (Jurnal Protobiont, 2019)
Long-tailed macaque (Macaca fascicularis) is one of the primates that can coexist with humans, but the use of land into human settlements can lead to reduced habitat for long-tailed monkeys and cause monkeys to disturb humans. This study was conducted to determine the disturbances of long-tailed macaque (Macaca fascicularis)in Tumuk Manggis and Tanjung Mekar Villages, Sambas District, West Borneo. This study used in-depth interviews method to collection data of disturbance. Data collected were analyzed quantitative descriptively. The results showed that the disturbances carried out by long-tailed macaque when entering the residential area are to steal fruit or food at the people’s plantations or the backyard of people’s homes.The forest in the study area does not provide abundant feed and the land that is converted into a building allows long-tailed monkeys to enter residential areas.